Validating the Philadelphia Mindfulness Scale [PMS] for Those with Fibromyalgia. Issue 3 (2nd October 2015) - Taylor, Peter J.; Bourne, Kathryn; Eames, Catrin; Dickson, Joanne M.
Abstract: Objectives: Dispositional mindfulness [DM] has become an important construct in understanding and treating fibromyalgia. However, few DM measures exist that have been validated in those with fibromyalgia. The Philadelphia Mindfulness Scale [PMS] is a self-report of DM. In the current study, we validate the PMS within a sample of individuals with fibromyalgia. Design: This was a cross-sectional online study. This enabled the recruitment of a larger sample of individuals with experiences of fibromyalgia than may have been achieved through face-to-face assessment. A cross-sectional approach was adopted to minimise resource demands. Method: The PMS alongside measures of fibromyalgia severity [The Revised Fibromyalgia Impact Questionnaire], affect [Positive and Negative Affect Scale] and decentring [Experiences Questionnaire] were completed online by a sample of N  = 936 individuals with fibromyalgia. Results: Confirmatory factor analysis supported a revised three-factor structure for the PMS. This factor structure excluded items which could overlap with hypervigilance within fibromyalgia. The three supported factors were Awareness, Non-judging/Control and Non-suppression/reactivity. Concurrent validity of the subscales was partially supported via correlations with positive affect [PA] and negative affect [NA] and decentring. Conclusions: The results support the use of the PMS in individuals with fibromyalgia, and in particular the use of this measure to compare those with and without experience of meditation. The PMS may be a useful tool in evaluating mindfulness-based interventions [MBIs] within this population. Limitations: The online design prevented more in-depth assessment of fibromyalgia. As the study was cross-sectional, test re-test reliability could not be assessed.